Statistical convergence of double sequences on product time scales - Çinar, Muhammed; Yilmaz, Emrah; Altin, Yavuz; Gulsen, Tuba (De Gruyter, 2019)
In this study, we present the basic concepts of statistical convergence for double sequences on an arbitrary product time scale. Moreover, we investigate the connection between statistical convergence for double sequences and double Cesàro summability on a product time scale. © 2019 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: Cesàro summability; double sequences; Statistical convergence; time scales